Triage Knowledge and Practice and Associated Factors Among Emergency Department Nurses - Mohammad AlShatarat RN, MsN; Ahmad Rayan RN, CNS, PhD; Nidal F. Eshah RN, CNS, PhD; Manal Hassan Baqeas RN, MSN; Mohammad Jamil Jaber RN, MsN; Mohammed ALBashtawy PhD, MPH, RN (SAGE Publishing, 2022)
Objective The study aims at assessing the triage knowledge and practices and their associated factors among emergency department nurses employed in King Fahad Medical City (KFMC), Saudi Arabia. Method The study employed a cross-sectional, descriptive, and correlational design. Data collection was carried out from February 11, 2021, until April 27, 2021. The study included all emergency department nurses who were working in the KFMC during the data collection period and excluded those who were on leave at the time of data collection. A self-reported questionnaire with adequate validity and reliability was used. Statistical analysis was performed using the IBM SPSS Version 25 employing descriptive statistics, independent t -test, one-way ANOVA, and Pearson correlation test. Results A total of 147 emergency department nurses completed the study. Participants demonstrated generally high levels of triage knowledge and triage practice. However, knowledge deficit and incorrect practice related to some aspects were noted. There were no significant differences in triage knowledge and practice according to participants' demographics including gender, job title, qualification, emergency nursing training, and previous training in triage ( P  > 0.05). Most participants ( n  = 141, 95.9%) had access to their triage systems and the majority ( n  = 79, 53.7%) utilize triage systems on a daily basis. Half said that only professional nurses performed the triage role ( n  = 69, 46.9%). There was a significant positive relationship between triage knowledge and practice (r = 0.486, P  < 0.01). Conclusion The respondents had a high level of triage knowledge and practice. However, they have some areas of knowledge deficit and some deficiencies in the conversion of their knowledge into practice. The study recommends the development of further training and education in emergency nursing to address knowledge deficits and incorrect triage practices.